1998
DOI: 10.1093/emboj/17.11.3091
|View full text |Cite
|
Sign up to set email alerts
|

Direct binding of Smad3 and Smad4 to critical TGFbeta -inducible elements in the promoter of human plasminogen activator inhibitor-type 1gene

Abstract: Smad proteins play a key role in the intracellular signalling of transforming growth factor β (TGFβ), which elicits a large variety of cellular responses. Upon TGFβ receptor activation, Smad2 and Smad3 become phosphorylated and form heteromeric complexes with Smad4. These complexes translocate to the nucleus where they control expression of target genes. However, the mechanism by which Smads mediate transcriptional regulation is largely unknown. Human plasminogen activator inhibitor-1 (PAI-1) is a gene that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

82
1,630
5
5

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,679 publications
(1,722 citation statements)
references
References 58 publications
(68 reference statements)
82
1,630
5
5
Order By: Relevance
“…We also confirmed that ELAC2 dosedependently potentiated TGF-b-induced (ARE) 2 -luc activity ( Figure 1c) although the effect of ELAC2 on TGF-b-induced (ARE) 2 -luc activity was lower than that on ALK5ca-induced (ARE) 2 -luc activity. (CAGA) 12 -luc is known to be activated by TGF-b-induced complex between Smad3 and Smad4 (Dennler et al, 1998). When we explored if ELAC2 can activate the TGF-b/Smad3-dependent promoter, ELAC2 could also potentiate the activity of (CAGA) 12 -luc upon ALK5 activation in dose-dependent manner ( Figure 1d).…”
Section: Elac2mentioning
confidence: 99%
See 1 more Smart Citation
“…We also confirmed that ELAC2 dosedependently potentiated TGF-b-induced (ARE) 2 -luc activity ( Figure 1c) although the effect of ELAC2 on TGF-b-induced (ARE) 2 -luc activity was lower than that on ALK5ca-induced (ARE) 2 -luc activity. (CAGA) 12 -luc is known to be activated by TGF-b-induced complex between Smad3 and Smad4 (Dennler et al, 1998). When we explored if ELAC2 can activate the TGF-b/Smad3-dependent promoter, ELAC2 could also potentiate the activity of (CAGA) 12 -luc upon ALK5 activation in dose-dependent manner ( Figure 1d).…”
Section: Elac2mentioning
confidence: 99%
“…Flag-Smad2 mutants were generously gifted by Dr T Imamura (Cancer Institute, Japan). The constructs for pcDEF3-Flag-Smad2, pcDEF3-myc-Smad2, pcDNA3-6xMyc-Smad2, pcDEF3-Flag-Smad3, pcDEF3-Flag-Smad4, 2xARE-luc, (CAGA) 12 -luc and GST-Smad2 have been described previously (Dennler et al, 1998;Kawabata et al, 1998;Itoh et al, 2000Itoh et al, , 2003. pGEX-4T-1 (GST alone) and CH110 were purchased from Amersham, Buckinghamshire, England.…”
Section: Expression Plasmidsmentioning
confidence: 99%
“…After phosphorylation by the receptor, Smads form heteromeric complexes with Smad4, a constitutively phosphorylated common mediator of the two pathways. The Smad complexes then translocate to the nucleus where they control expression of diverse genes (Derynck and Feng, 1997;Dennler et al, 1998;Jonk et al, 1998). Smad4 is the unique member of the second class of Smad proteins: central ones.…”
mentioning
confidence: 99%
“…The N-terminus MH1 domain of Drosophila Mad (Kim et al, 1997), Smad3 and Smad4 (Yingling et al, 1997;Dennler et al, 1998;Zawel et al, 1998) binds DNA and shows no homology with other known DNA binding domains. The C-terminus MH2 domain interacts with the receptor and displays transcriptional activity when fused to a heterologous Gal4 DNA-binding domain (Liu et al, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation